Effects of Injury Severity and Brain Temperature on KAT6A Expression after Traumatic Brain Injury in Rats - Dilirebati Dilimulati; Lin Zhang; Yourong Duan; Feng Jia (BIO Integration, 2022)
Background: Traumatic brain injury (TBI) is associated with a range of neural changes. A comprehensive understanding of the injury-induced lysine acetyltransferase 6A (KAT6A) response, particularly the temporal profile of biochemical alterations, is crucial to design effective therapeutic interventions. Methods: Experiments were performed in male Sprague-Dawley rats. The influence of post-traumatic hypothermia (32°C) or hyperthermia (39°C) on the temporal and regional expression profiles of KAT6A was assessed after moderate or severe TBI. qPCR and western blotting were used to determine the expression of KAT6A in different groups. Results: In the ipsilateral and contralateral hemispheres, significantly lower protein and mRNA expression of KAT6A was found after TBI than sham injury. Moreover, two expression minima of KAT6A were observed in the cortex and hippocampus of the ipsilateral hemisphere. A decrease in injury severity was associated with lower levels of KAT6A mRNA at 12 h and protein at 24 h, but KAT6A mRNA at 48 h and protein at 72 h had alterations. Compared with normothermia and hyperthermia, post-traumatic hypothermia intensified the decrease in KAT6A at both the mRNA and protein levels. In contrast, hyperthermia, as compared with normothermia, did not significantly affect the levels of KAT6A mRNA at 12 h and protein at 24 h, but triggered a significant increase in levels of KAT6A mRNA at 24 h and protein at 72 h. Furthermore, an overall upregulation of KAT6A after TBI was associated with greater injury severity in a time-dependent manner. Conclusions: Post-traumatic hypothermia plays a key role in the regulation of KAT6A expression and thus may at least partially explain the phenotype of post-traumatic temperature in secondary injury after TBI.